Propuesta de ecobarrio adaptable en zonas periféricas de Riobamba, caso de estudio subsector Z14 - A - Salazar Alvear, Andrew Josue (2026)
This research proposes the design of an adaptable eco-neighborhood on the outskirts of Riobamba, using Subsector Z14-A as a case study. The objective is to address the need for sustainable urban development in the area, as well as the various challenges present in this type of zone. The proposal is based on a comprehensive understanding of the territory through urban and sustainability criteria. The study employs territorial analysis to identify sector dynamics, recognize strategic opportunities, and define the most suitable area for intervention. The different stages of the research required the use of both quantitative and qualitative methodologies. The project is structured around essential components such as site integration, mobility, the creation of inclusive public spaces, waste reduction, and mixed-use diversity—key elements for fostering a balanced and efficient urban environment. Furthermore, the characteristics and needs of the local population are incorporated, ensuring that the project responds to their way of life and promotes social cohesion.